2018
DOI: 10.3892/ijmm.2018.3986
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure carbon dioxide pneumoperitoneum induces oxidative stress and mitochondria-associated apoptotic pathway in rabbit kidneys with severe hydronephrosis

Abstract: The primary aim of the present study was to investigate the potential effect of high-pressure carbon dioxide (CO2) pneumoperitoneum on kidneys with severe hydronephrosis and to investigate the possible underlying mechanism. A total of 18 rabbits underwent a surgical procedure inducing severe hydronephrosis. Rabbits were then divided at random into three groups (n=6 each) and subjected to intraabdominal pressure of 0, 8 or 18 mmHg, respectively. CO2 inflation lasted for 90 min in the pneumoperitoneum groups. Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…Mitochondrial morphological and functional impairment during pneumoperitoneum has been shown to be involved in multiple organ injury [ 13 , 49 ]. Herein, we found that during pneumoperitoneum, excessive pressure and prolonged exposure led to mitochondrial swelling, vacuolization, and fragment, which was consistent with previous studies [ 13 , 50 ]. Multiple studies have demonstrated that mitochondrial DNA (mtDNA) is released after mitochondria are impaired [ 51 ], and mtDNA content has been shown to reflect the degree of mitochondrial dysfunction in response to cellular stress injury [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondrial morphological and functional impairment during pneumoperitoneum has been shown to be involved in multiple organ injury [ 13 , 49 ]. Herein, we found that during pneumoperitoneum, excessive pressure and prolonged exposure led to mitochondrial swelling, vacuolization, and fragment, which was consistent with previous studies [ 13 , 50 ]. Multiple studies have demonstrated that mitochondrial DNA (mtDNA) is released after mitochondria are impaired [ 51 ], and mtDNA content has been shown to reflect the degree of mitochondrial dysfunction in response to cellular stress injury [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Mixed acute-and-chronic injury, where toxic exposures, disease states, and/or assessments were both acute (i.e., hours, days) and chronic (i.e., weeks, months, years) in the same study, were observed in human transplant rejection (biopsy 1 week to 3 years post-transplant) [ 88 ], swine hepatitis E virus infection (7 and 14 days post-inoculation) [ 52 ], CO 2 pneumoperitoneum-induced stress in hydronephrotic kidneys (2 weeks hydronephrosis, 2 days post-pneumoperitoneum) [ 53 ], mesangial proliferative glomerulonephritis induced by snake venom (1 to 14 days post-injection) [ 99 ], unilateral ureteral obstruction (1 to 14 days of obstruction) [ 100 ], uranyl acetate exposure (1 to 28 days of exposure) [ 101 ], aristocholic acid nephropathy (5 and 30-day daily exposure) [ 102 ], and neonatal hyperoxia (tested 1 to 60 postnatal days, exposed to hyperoxia first 14 days) [ 103 ]. Fourteen days after impact is a very common assessment time point for these kinds of kidney injuries [ 52 , 53 , 99 , 101 , 103 ]. In the majority of cases, TUNEL-positive cells were localized in tubules and collective ducts.…”
Section: Tunel Applicationsmentioning
confidence: 88%
“…TUNEL is applicable to all cell types, organs, and species that have DNA and DNases, which includes just about all species. TUNEL has been used to identify and quantify kidney injury in a wide array of animals, including zebrafish [ 50 ], Japanese rice fish [ 51 ], chickens [ 48 ], gerbils [ 52 ], mice [ 41 ], rats [ 45 ], rabbits [ 53 ], mini-pigs [ 54 ], and humans [ 55 ]. An important advantage of TUNEL is that it can be used in fixed cultured cells as well as fixed tissues.…”
Section: Tunel Applicationsmentioning
confidence: 99%
See 2 more Smart Citations